2021
DOI: 10.1007/s11205-021-02777-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolitical Versus Political Participation: Longitudinal Associations with Mental Health and Social Well-Being in Different Age Groups

Abstract: Drawing on public opinion and empirical research, one may advise people to participate in voluntary organizations because voluntary participation can improve their mental health and social well-being. However, do such benefits apply across different types of participation and across the life course? In this study, we investigated whether benefits to mental health and social well-being differ between nonpolitical and political participation and across age groups (preregistration is accessible at https://osf.io/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Successful aging involves active engagement with life ( Rowe & Kahn, 1997 ). Political activity may have a profound positive impact on well-being and life satisfaction ( Lühr et al, 2022 ; Pavlova & Lühr, 2023 ). However, political group attendance may also be associated with poor mental health among older adults, particularly those residing in politically competitive regions.…”
Section: Discussionmentioning
confidence: 99%
“…Successful aging involves active engagement with life ( Rowe & Kahn, 1997 ). Political activity may have a profound positive impact on well-being and life satisfaction ( Lühr et al, 2022 ; Pavlova & Lühr, 2023 ). However, political group attendance may also be associated with poor mental health among older adults, particularly those residing in politically competitive regions.…”
Section: Discussionmentioning
confidence: 99%
“…The results were therefore interpreted such that changes in volunteering impact changes in life satisfaction. However, the direction of effects could not be established with this methodological approach and although it may be less plausible, a reverse interpretation is at least possible (e.g., Bjälkebring et al, 2021;Lawton et al, 2021;Lühr et al, 2022aLühr et al, , 2022b: that changes in mental health have influenced changes in volunteering, particularly in retirement-for instance because volunteering is driven by work-or family-related obligations prior to retirement and is more likely a matter of individual constitution during retirement. Nevertheless, I controlled extensively for health by including it as a time-varying covariate.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite this reasonable explanation, recent longitudinal studies with robust designs (i.e., fixed-effects models, within-person analyses) have suggested that the effects of volunteering on mental health among older adults are surprisingly small and not significantly stronger than the effects for younger adults (Lawton et al, 2021;Lühr et al, 2022aLühr et al, , 2022b.…”
Section: Introductionmentioning
confidence: 98%
“…Life satisfaction refers to people’s evaluation of the overall quality of life [ 9 ]. It can be evaluated based on emotions, satisfaction with other people’s relationships, achieved goals, self-concept, self-perceived daily life ability, as well as social support and community belonging [ 10 ]. Life satisfaction can also reflect experiences that have a positive impact on a person [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%